Types of smartphone usage and problematic smartphone use among adolescents: A review of literature - Sii Jiing Chan; Kee Jiar Yeo; Lina Handayani (Institute of Advanced Engineering and Science, 2023)
This review aimed to provide an overview of the influence of social and process smartphone use on problematic smartphone use (PSU) among adolescents aged between 10-24 years old. Social smartphone use comprises three types of smartphone features: social networking sites, chatting/texting/instant messaging, and video/phone calls. On the other hand, categories of process smartphone use include watching videos/television/movies, web surfing, playing games, listening to music/podcasts/radio, and educational learning. There were 42 studies with a total of 139,389 adolescents met the criteria for inclusion after a thorough search of academic databases. Overall, the evidence from the studies included in this review revealed that chatting/texting, video/phone calls, watching videos/television/movies and music/podcasts/radio were positively and significantly linked to and predicted problematic smartphone use. Social networking sites use, instant messaging, gaming, web surfing and educational learning yielded inconsistent results. They could have a positive or negative relationship with PSU and play a role in predicting PSU. More research is needed for music/podcasts/radio and video/phone calls because the results are still scarce.